Efficacy and Safety of Antiplatelet Agents for Adult Patients With Ischemic Moyamoya Disease - Ye, Fei; Li, Jiaoxing; Wang, Tianzhu; Lan, Kai; Li, Haiyan; Yin, Haoyuan; Guo, Tongli; Zhang, Xiong; Yang, Tingting; Liang, Jie; Wu, Xiaoxin; Li, Qi; et al. (Frontiers in Neurology, 2021)
Background: The use of antiplatelet agents in ischemic moyamoya disease (MMD) is controversial. This study aimed to investigate the effectiveness and safety of antiplatelet therapy compared with conservative treatment and surgical revascularization in ischemic MMD patients. Methods: Ischemic MMD patients were enrolled from eight clinical sites from January 2013 to December 2018. Follow-up was performed through clinical visits and/or telephone interviews from first discharge to December 2019. The primary outcome was the episodes of further ischemic attacks, and the secondary outcome was the individual functional status. Risk factors for future stroke were identified by the LASSO-Cox regression model. Propensity score matching was applied to assemble a cohort of patients with similar baseline characteristics using the TriMatch package. Results: Among 217 eligible patients, 159 patients were included in the analyses after a 1:1:1 propensity score matching. At a mean follow-up of 33 months, 12 patients (7.5%) developed further incident cerebral ischemic events (surgical:antiplatelet:conservative = 1:3:8; p=0.030), 26 patients (16.4%) developed a poor functional status (surgical:antiplatelet:conservative = 7:12:7; p=0.317), and 3 patients (1.8%) died of cerebral hemorrhage (surgical:antiplatelet:conservative = 1:2:0; p=0.361). The survival curve showed the risk of further cerebral ischemic attacks was lowest with surgical revascularization, while antiplatelet therapy was statistically significant for preventing recurrent risks compared with conservative treatment (X2=8.987; p=0.011). No significant difference was found in the functional status and bleeding events. The LASSO-Cox regression model revealed that a family history of MMD (HR=6.93; 95% CI: 1.28-37.52; p=0.025), a past history of stroke or transient ischemic attack (HR=4.35; 95% CI: 1.09-17.33; p=0.037), and treatment (HR=0.05; 95% CI: 0.01-0.32; p=0.001) were significantly related to the risk of recurrent strokes. Conclusions: Antiplatelet agents were effective and safe in preventing further cerebral ischemic attacks in adult patients with ischemic MMD. They may be a replacement therapy for patients with surgical contraindications and for patients prior to revascularization.